AVALIAÇÃO DE ATRIBUTOS FÍSICOS EM DIFERENTES SISTEMAS DE PRODUÇÃO EM UM ARGISSOLO VERMELHO - CENTENARO, Felipe Silva; DA SILVA, Marcos Antonio Camacho; PANACHUKI, Elói; JUNIOR, Sérgio Bortoloto; DE OLIVEIRA, Jean Carlos Lopes (ANAIS DO ENIC, 2017)
-